Case Study on Community Empowerment thru Panca Daya Waste Bank - Hadrizal, Zul; Setiawati, Setiawati (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This study aims to examine the community empowerment process carried out by the Panca Daya. This initiative is believed to stem from the success of the Panca Daya Waste Bank in empowering the community through waste management. The research is a qualitative method with a case study approach. Primary data sources consist of key informants, including managers of the Panca Daya Waste Bank and other individuals familiar with the community empowerment process, while secondary data sources include documents, articles, and journals. Informants were selected using the snowball sampling technique. The researcher served as the main instrument, utilizing interviews, observations, and documentation as data collection methods. Data analysis techniques used include data reduction, data presentation, and conclusion drawing. To ensure data validity, the researcher applied triangulation of data, methods, and theories. The findings of this study indicate that the community empowerment process carried out by the Panca Daya Waste Bank involves three main aspects. In the aspect of knowledge development, (1) the efforts include conducting needs identification and analysis, (2)  organizing socialization and outreach programs, and (3)  forming discussion groups. In the aspect of participation enhancement, (1) the process is carried out by leveraging social media and digital platforms, (2) offering unique and attractive savings payment systems, and (3) holding recycling creativity competitions. Meanwhile, in the aspect of economic strengthening,(1)  the initiatives include providing training on product diversification, (2) developing products, and building partnerships.